The correlation between muscle strength, inhibitory function, and cognitive function in older adults with cognitive impairment: evidence from resting-state electroencephalography - Mi Hu; Xing Wang (Frontiers in Aging Neuroscience)
ObjectiveThis study explored the associations among muscle strength, inhibitory control, and cognitive function in older adults with cognitive impairment, focusing on related EEG changes.MethodsAmong 247 adults aged 70 and above, 120 with cognitive impairment were included. Assessments included the Montreal Cognitive Assessment (MoCA), Stroop task, grip strength, and resting-state EEG.ResultsInhibitory control was significantly related to cognitive function: accuracy in congruent (r = 0.599, p < 0.001) and incongruent (r = 0.474, p < 0.001) conditions correlated positively with MoCA scores, while response times in both conditions showed negative correlations (r = –0.475 and –0.354, respectively, p < 0.001). EEG alpha1 (C3, P3, F7), alpha2 (P3, F8), and beta1 (P3, F7) power were significantly associated with both cognitive and inhibitory performance. Muscle strength was significantly positively correlated with specific EEG indicators, particularly alpha1 power at C4 (r = 0.212, p < 0.05), O2 (r = 0.204, p < 0.05), F8 (r = 0.225, p < 0.05), and T6 (r = 0.206, p < 0.05), as well as alpha2 power at C3 (r = 0.216, p < 0.05), P3 (r = 0.222, p < 0.05), P4 (r = 0.268, p < 0.001), F8 (r = 0.284, p < 0.001), and T5 (r = 0.218, p < 0.05).ConclusionMuscle strength may support cognitive and inhibitory function by influencing specific EEG activities. These findings highlight the neurophysiological links among muscle strength, cognition, and brain activity, offering potential biomarkers for early detection and intervention in cognitive decline.